Regulasi dan Tantangan Pemanfaatan AI dalam Moderasi Beragama - Khusnul Khatimah; Fanti Rahmania Ramli; Kurniati Kurniati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Artificial Intelligence (AI) is a technology that has had a significant impact on various aspects of life, including science. Recent developments in AI have shifted the traditional boundaries of knowledge production and distribution, including in the religious realm. This research aims to fill the epistemological gap in contemporary Islamic legal thought by offering an integrative framework between traditional ijtihad and supervised digital ijtihad practices. This research uses a normative-qualitative (juridical-normative) approach. The researchers found that AI has the potential to be an effective tool for strengthening religious moderation, particularly through digital education, the dissemination of messages of tolerance, and the dissemination of counter-narratives against radicalism. For example, da'wah chatbots and digital interpretation applications can expand moderate religious literacy. However, the research also highlights various challenges, including epistemological issues stemming from AI's lack of a scientific chain of command, the risk of shifting authority from scholars to technology, and the lack of legal regulations governing responsibility for AI-generated religious content. Therefore, specific regulations and collaboration between scholars, the government, and technology developers are needed to ensure that AI continues to support the maqāṣid al-Shari'ah (the principles of Islamic law) and religious moderation.